Digital Revolution and the Prospects for Online Political Communication: A Review of Political Parties ’ Social Media Status in Tanzania - Babeiya, Edwin Ernest; Magoti, George Mashauri (University of Dar es Salaam Library Journal, 2023)
A revolution in information and communication technology has introduced social media as alternative platforms through which political parties can interact with the public. Political parties ' success in using these avenues depends on the online strategies applied. Tanzania has not been an exception in the use of social media as political parties have been using them for political activities. However, little is known regarding the way political parties have established themselves on social media platforms. Using the equalization, normalization, and hybrid perspectives as an analytical framework, this paper examines the status of Tanzania ' s political parties in social media. The data obtained through the review of social media pages, key informant interviews and documentary analysis reveal that although political parties have been using social media for political activities, the profile of their social media status is low. The findings further show that social media have not altered the balance of power among political parties in Tanzania as the social media profile of opposition political parties does not significantly differ from that of the ruling party CCM as revealed by the number of their social media pages, followers and posts as well testimonies through interviews regarding social media usage. Several factors including political parties ' limited awareness of the potential of social media, the unpredictability of the political system as well as resource constraints are attributed to this status. To overcome these challenges, a call is made for policy and capacity building interventions to empower political parties and the citizenry for effective online engagement.